PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU SOSIAL (SISWA KELAS VII SMP NEGERI 8 PEKANBARU) - Rizki Bunda Liza Putri; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the purpose of this research is to know the parenting pattern that applied to the student, to know the level of student’s social behavior, and to know the relation of parenting pattern with the social behavior of students in the SMPN 8 Pekanbaru.This research is a research with contingency chi squared design using quantitative approach. The sample used is 188 respondents in this study selected by using probability sampling with random sampling technique. Data retrieval techniques in this study using a questionnaire method, to collect parenting data applied by parents with social behavior of students. In data analysis techniques using the contingency chi square formula. The result of the research coducted on 188 respondents found that most parents use authoritarian parenting pattern with good social behavior of 61 respondents (32,45%) and parenting authoritarian parents with bad social behavior of 45 respondents (23,94%). Statistic test obtained chi square calculated bigger than table (264,15>9,488) Ho rejected Ha accepted meaning parenting have significant relation with social behavior of child equal to 0,76. Parenting patterns affect the child’s social behavior. For it is suggested to parents to give more attention on children through parenting which apply parenting and also due to social behavior child could to shape with good.Key word: parenting parents, social behavior